Newcastle disease in pigeon review article - Muhammadtahir Abdulrasool; Waleed Seger (Basrah Journal of Veterinary Research)
Newcastle disease (ND) is a viral disease of poultry and other bird species like pigeon (Columbi livia), it characterizes as devastating and contagious and it has been distributed worldwide. ND in pigeons is caused by pigeon paramyxovirus type 1(PPMV-1) which is an antigenic and host variant of the avian paramyxovirus serotype 1 (APMV-1), the disease in pigeons is termed paramyxovirosis and cause nervous signs with high mortality usually in the bird with kidneys infected with viscerotropic strains, and neural signs appeared individually. PPMV-1 was initially detected by hemagglutination activity (HA) and confirmed with hemagglutination inhibition assay (HI), and molecular-based techniques. Serological diagnosis of paramyxovirosis is necessary because of the similarity of the PPMV-1 infection with sodium chloride poisoning, pigeon herpes virus infection (PHV), and ornidazole overdose that cause same neurological signs. PPMV-1 infection can be controlled effectively by vaccination by specific vaccines associated with good biosecurity aspect